The Implementation of the STAD Learning Model Assisted by PowToon on Solid Geometry to Improve the Learning Outcomes of Eighth-Grade Students - Ajeng Sri Hadimiati; Asrul Asrul (MASI Mandiri Edukasi, 2025)
This study aimed to address eighth-grade students' low conceptual understanding and problem-solving skills in learning flat-sided solid figures by applying the STAD learning model assisted by Powtoon. A quasi-experimental method with a Nonequivalent Control Group Design was employed, with samples selected using cluster sampling from SMP Muhammadiyah 01 Medan. Research instruments consisted of pretest and posttest essay questions. The results showed that the experimental class obtained a higher mean N-Gain score of 0.65 (medium category) than 0.38 (medium category) in the control class. The independent samples t-test revealed that the difference was statistically significant (t = 3.142, df = 48, p = 0.003 < 0.05, t-table = 2.011). These findings indicate that implementing the STAD model, assisted by Powtoon, effectively enhanced students’ conceptual understanding and mathematical problem-solving skills. Moreover, it suggests that cooperative learning supported by interactive animations can serve as an effective alternative to foster more active, collaborative, and meaningful mathematics learning in secondary schools.